The influence of leadership style, work environment, and job satisfaction on employee performance through work motivation as a moderating variable in the PT. PLN (Persero) UP3 Bima UIW NTB - Sitompul, Adrian; Supriyadi, Supriyadi; Citra, Fitriah Permata (Journal of Economics and Business Letters, 2024)
The purpose of this study is to determine whether leadership style, work environment, and job satisfaction influence employee performance both directly and indirectly through work motivation during PT. PLN (Persero) UP3 Bima UIW NTB. This study used a quantitative approach by collecting data in the form of numbers. The sample used was 110 respondents, using a saturated sampling technique. In this study, partial least squares (PLS) data analysis was performed using the Smart PLS software. The results of the study indicate that leadership style has a negative and significant effect on employee performance; work environment has a positive and significant effect on employee performance; job satisfaction has a positive and significant effect on employee performance; leadership style through work motivation has a positive and significant effect on employee performance; work environment through work motivation has a negative and significant effect on employee performance; and job satisfaction through work motivation has no effect and is not significant on employee performance at PT. PLN (Persero) UP3 Bima UIW NTB.